Tenapanor for the treatment of irritable bowel syndrome with constipation. Issue 5 (3rd May 2020) - Sinagra, Emanuele; Rossi, Francesca; Raimondo, Dario; Conoscenti, Giuseppe; Anderloni, Andrea; Guarnotta, Valentina; Maida, Marcello
ABSTRACT: Introduction: Irritable bowel syndrome with constipation is associated with higher rates of functional impairment, as compared to other subtypes of the syndrome. Conventional laxative-based pharmacologic therapy of IBS-C, which is mostly symptom-based, is often unsatisfactory. Tenapanor represents a first-in-class orally available inhibitor of NHE3, which is minimally absorbed in the GI tract, what constitutes a significant therapeutic benefit, as it may act on the drug target. Areas covered: Aim of this article is to sum up the evidences about pharmacodynamics and pharmacokinetics of tenapanor, focusing on animal models and in vitro studies, but also discuss clinical trials on tenapanor's safety and efficacy in view of its important potential role in IBS-C treatment. Expert opinion: In the challenging setting of irritable bowel syndrome with constipation, tenapanor represents a novel strategy in the pipeline of the therapies of IBS-C. Its pharmacokinetic and pharmacodynamic profile provides that it is minimally absorbed from the intestinal lumen and that its action is local, but not systemic action, therefore guaranteeing the reduction of drug–drug interactions, toxicity and severe adverse effects. Phase 2b and 3 trials showed an optimal satisfaction of primary and secondary endpoints.